The General Condition of Agriculture in Kalmykia at the beginning of collectivization - Namsyr A. Shikhanov (Монголоведение)
Introduction. This article examines the general state of agriculture in the Kalmyk Autonomous Region by the end of the 1920s (before the beginning of collectivization) in comparison with the corresponding indicators of previous periods. The study is based on the analysis of statistical data, documents and other sources that allow us to assess the level of agricultural development in this region during the specified period. The purpose of the study: to consider and analyze the state of agriculture in Kalmykia on the eve of continuous collectivization. The source base of the research is based on archival documents of the National Archive of the Republic of Kalmykia. Results. The article analyzes the state of agriculture in the Kalmyk Autonomous Region by the end of the 1920s in comparison with statistical data from various historical periods: on the eve of the First World War, during the Civil War and the NEP. The analysis showed that the agriculture of the Kalmyk Autonomous Region, which suffered significant damage during the Civil War and famine of 1921–1922, managed to recover in almost all directions during the years of the NEP, although it did not reach pre-revolutionary indicators.